How to speak the same language with European innovation-policy in terms of living labs? Kuidas innovatsioonipoliitikas eluslaborite (living labs) kontekstis Euroopaga sama keelt rääkida? - Lepik, Ave; Varblane, Urmas (Estonian Discussions on Economic Policy, 2010)
A Living Lab is a user driven open innovation ecosystem, which combines consumers, firms and public sector. It is a rather new innovation methodology, which steadily gains stronger acceptance and becomes a significant innovation policy’s instrument in many countries. This article provides suggestions and conceptual framework for the applying living lab as the innovation policy instrument in the framework of national innovation-system in small countries. In the countries with the total lack or very limited experience about using the living labs the introduction of living lab approach requires answering several important questions. The paper is focused on the identification of potential areas of using living labs approach as well highlighting also potential obstacles in the process of its application in Estonia